Delayed Supplementation Strategy of Extracellular Vesicles from Adipose-Derived Mesenchymal Stromal Cells with Improved Proregenerative Efficiency in a Fat Transplantation Model - Shan Mou; Yuan Li; Di Sun; Muran Zhou; Jialun Li; Lifeng Chen; Shaokai Liu; Jie Yang; Peng Xiao; Jing Tong; Zhenxing Wang; Jiaming Sun (Stem Cells International)
Background. Mesenchymal stromal cells (MSCs) and their secreted extracellular vesicles (MSC-EVs) possess similar proregenerative effects when injected into defects immediately following trauma. However, MSC-EVs are superior to MSCs in terms of storage and rejection reflection, while immediate administration of MSC-EVs is related to several target cells for most donor cells die within few weeks. Besides, the inflammatory cascade is incited, providing an unfavorable environment for target cells. We hypothesized that delayed injection of MSC-EVs might have priority on tissue regeneration than instant injection. Method. Extracellular vesicles isolated from adipose-derived mesenchymal stromal cells (ADSC-EVs) were administered into human umbilical vein endothelial cells (HUVECs) in vitro at different doses. The migration of HUVECs was assessed using the scratch wound healing assay, whereas the length of tubes and number of vessel-like structures formed by HUVECs were determined using tube formation assay. Next, 24 BALB/c nude mice were randomly divided into three groups (n=8). For the EV-delayed group, ADSC-EVs were injected into transplanted fat a week later than the EV-immediate group. The volume and weight of grafts were measured at 3 months after fat transplantation. Further, the number of CD31-possitive vessels and CD206-possitive cells in the fat grafts was quantified. Results. Compared with the EV-immediate group, the EV-delayed group had a higher fat tissue retention volume (0.11±0.02 mL versus 0.08±0.01 mL), more neovessels (31.00±4.60 versus 24.20±3.97), and fewer cysts. Furthermore, there were more Ki67-positive cells (25.40±7.14 versus 16.20±4.17) and CD206-positive M2 macrophages cells (23.60±3.44 versus 14.00±3.85) in the EV-delayed group than in the EV-immediate group. Conclusion. Delayed injection of ADSC-EVs promotes fat graft volume retention by stimulating angiogenesis. These findings suggest that delayed supplementation might be a more effective strategy for the application of MSC-EVs in tissue regeneration.